HIF1α mediates circadian regulation of skeletal muscle metabolism and substrate preference in response to time-of-day exercise - Amy M. Ehrlich; Kirstin A. MacGregor; Stephen P. Ashcroft; Lewin Small; Ali Altıntaş; Alexander V. Chibalin; Matthias Anagho-Mattanovich; Ben Stocks; Thomas Moritz; Jonas T. Treebak; Juleen R. Zierath (Proceedings of the National Academy of Sciences, 2025)
The regulation of metabolism in peripheral tissues is intricately linked to circadian rhythms, with hypoxia-inducible factor-1α (HIF1α) implicated in modulating time-of-day-specific exercise responses. To investigate this relationship, we generated a skeletal muscle-specific HIF1α knockout (KO) mouse model and performed extensive metabolic phenotyping and transcriptomic profiling under both basal conditions and following acute exercise during early rest (ZT3) and active (ZT15) phases. Our findings reveal that HIF1α drives a more robust transcriptional and glycolytic response to exercise at ZT3, promoting glucose oxidation and mannose-6-phosphate production while potentially sparing fatty acid oxidation. In the absence of HIF1α, skeletal muscle metabolism shifts toward oxidative pathways at ZT3, with notable alterations in glucose fate. These results establish HIF1α as an important regulator of time-of-day-specific metabolic adaptations, integrating circadian and energetic signals to optimize substrate utilization. This work highlights the broader significance of HIF1α in coordinating circadian influences on metabolic health and exercise performance.